POPULATION GROWTH IN BATAM MUNICIPALITY AS THE FRONTIER AND OUTERMOST REGION AT THE BORDER BETWEEN INDONESIA-SINGAPORE-MALAYSIA - Hutasoit, Imelda (Universitas Airlangga, 2023)
The systematic and accurate data on population has become pivotal point to overview the development of population in particular region, so that it required to a conduct a study to explore the description of the population growth rate, the factors causing the high population growth rate, and the impact of the high population growth rate in Batam Municipality. This study was exploratory research with a qualitative approach to analyze the population phenomenon in Batam Municipality. Data were collected using observation, interview, documentation, and audio-visual material collection. Informants were determined by purposive sampling and snowball techniques. This study used the Spradley analysis model with four stages of analysis, such as domain, taxonomic, components, and cultural themes. The results showed that the population growth rate increased from 1980 to 2012, but began to decline since the decline in economic growth in 2013 which indicated that the population growth rate in Batam Municipality followed the pattern of economic growth. The high rate of population growth was due to the high number of in-migration (65%) and high birth rates (35%), because most migrants were in productive age. The high rate of population growth in Batam Municipality had caused various population problems, such as citizenship status, citizenship administration services, illegal housing, traffic congestion, clean water crisis, waste accumulation, potential loss of local ethnic values, potential ethnic conflict, and potential increased of crime rate in Batam Municipality.